A proposed framework to understand young Muslims’ extremism behavior - Hamsan, Hanina H.; D’ Silva, Jeffrey Lawrence; Abu Samah, Asnarulkhadi; Yaacob, Zamre; Tang, Sui Sum; Kamarudin, Nurul Akhtar; Kamaruddin, Nurani (Faculty of Human Ecology, 2022)
Numerous studies have shown that young people exhibit risk-taking behavior. However, few studies directly address the symptoms of extremism behavior. Any activity aimed at countering extremist behavior must begin with a clear understanding of the causes of such behavior. While exposure to a single risk factor is unlikely to lead to extremism, multiple risk factors are required for behavior as risky (ages 16 to 25 years). Extremism can refer to various issues, but the focus here is on radicalism, violence, and terrorism which fall within its remit. A qualitative approach: Content analysis and indepth interviews were used to obtain data. There are a total of 19 factors that have been identified as possible contributors to early extremist behavior among Muslim youth. Bronfenbrenner's ecological systems theories, uncertainty identity, and intentional fellowship models were discussed in a proposed framework.